Catalytic Peptides: the Challenge between Simplicity and Functionality. Issue 9 (24th August 2022) - Carvalho, Sara; Peralta Reis, David Q.; Pereira, Sara V.; Kalafatovic, Daniela; Pina, Ana Sofia
Abstract: Enzymes' machinery has been an inspiration for chemists. Peptides are vital players in the origin of life, being ancestors of complex enzymes. Even short peptides that are simple in terms of the number of residues are reprogrammable and built to encode chemical information for catalysis, substrate recognition, and molecular interactions. The combinatorial search of the sequence space led to identifying peptides with catalytic activities. However, most of these sequences remain unevolved, leading to modest rates in aqueous media. Short peptides present conformational flexibility, which is their primary liability for catalysis. To overcome this, supramolecular motifs and secondary frameworks are used as scaffolds to incorporate catalytic residues and improve their efficiency. This review discusses the strategies used to discover and evolve catalytic function in short peptides beyond the de novo design and the advantages of using these approaches to enhance catalysis. Abstract :